2022
DOI: 10.3390/polym14194034
|View full text |Cite
|
Sign up to set email alerts
|

Crushing Characteristics Comparison between Aluminum/CFRP and Aluminum/CFRP/Aluminum Hybrid Tubes

Abstract: This study experimentally investigated the axial crushing characteristics of the hybrid tubes with the configuration of aluminum/carbon fiber-reinforced polymer (CFRP) (1/1) and aluminum/CFRP/aluminum (2/1). The effects of geometry size and fiber lay-up sequence on the axial crushing energy-absorption performances and failure modes of the two types of hybrid tubes were compared. The results showed that the energy absorption of the specimens with [0°/90°] lay-up sequence was better than that of the ones with [4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The thickness of Al-out may influence its impact performance 46) . The results obtained were similar to Fie et al 81) who conducted the Al tube with different diameters in the axial crushing test 81) .…”
Section: Impact Test On Metalsupporting
confidence: 87%
See 3 more Smart Citations
“…The thickness of Al-out may influence its impact performance 46) . The results obtained were similar to Fie et al 81) who conducted the Al tube with different diameters in the axial crushing test 81) .…”
Section: Impact Test On Metalsupporting
confidence: 87%
“…The greater diameter of the Al tube exhibited better energy absorption and peak crushing force. It can be concluded that the thickness of the Al tube influenced the impact performance 46,81) . On the other hand, the transition condition or buckling shape of the alloy tube subjected to axial impact loading was influenced by impact velocity [82][83][84] , striking mass 82,83) , material characteristic 84) and the width-to-thickness ratio 86) .…”
Section: Impact Test On Metalmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, several typical indicators such as energy absorption (EA), specific energy absorption (SEA), peak crushing force (PCF), mean crushing force (MCF), and crushing force efficiency (CFE) were used to assess the crashworthiness. 52,53 The PCF indicates the peak load during crushing test. The EA is the total energy absorbed throughout the crushing test, defined as:…”
Section: Quasi-static Crushing Testmentioning
confidence: 99%